An Instructional Design to Improve Students’ Higher Order Thinking Skills in Linear Programming - Nurherdiati, Ratna (J-PiMat : Jurnal Pendidikan Matematika, 2022)
The purpose of this study is to provide an instructional design for improving students' Higher Order Thinking Skills (HOTS) in linear programming. The method used in writing this article is the literature review method consisting of books and articles. The results showed that the development of an instructional design through the Model Eliciting Activities (MEAs) approach was effective in increasing student HOTS in mathematics learning. MEAs guide students to mathematically model based on context or real problems, break them down into separate parts, then understand the relationships between these parts, and interpret the results of student construction.